HUBUNGAN ANTARA POLA MAKAN DAN KENAIKAN BERAT BADAN MINIMUM DAN STATUS GIZI DI ANTARA ANAK-ANAK BERUSIA 2-5 TAHUN DI PUSAT KESEHATAN MASYARAKAT PANDANWANGI - choirul, delvingga13; Hastuti, Apriyani Puji; Isppriantari, Akoysia (Program Studi Keperawatan, Fakultas Ilmu Kesehatan, ITSK RS dr Soepraoen, 2025)
Introduction: This study aims to examine the relationship between eating patterns, minimal weight gain, and nutritional status among children aged 2–5 years. The research was conducted due to the persistent nutritional challenges in early childhood, which are often influenced by family eating habits. Methods: cross-sectional design was used with a total sampling of 65 children at Pandanwangi Health Center. Data were collected using an eating pattern questionnaire, minimal weight measurements, and nutritional assessments based on anthropometric standards. Results: The results indicated that most children had adequate eating patterns, experienced weight gain, and had good nutritional status. Chi-Squareanalysis showed no significant relationship between eating patterns and minimal weight gain or nutritional status.Conclusion: The study concludes that growth and nutritional outcomes are influenced by multiple factors beyond eating patterns, highlighting the need for comprehensive interventions through parental education and routine growth monitoring.